0760 Excessive daytime sleepiness, positive airway pressure, and patient satisfaction with multiple aspects of care in a real-world population with obstructive sleep apnea. (25th May 2022) - Parthasarathy, Sairam; Hyman, Danielle; Doherty, James; Saad, Ragy; Zhang, Jerrry; Morris, Susan; Eldemir, Lev; Fox, Benjamin; Vang, Mai Ka Ying; Schroeder, Jessica; Marshall, Nell; Parks, Gregory
Abstract: Introduction: Excessive daytime sleepiness (EDS) is common in patients with obstructive sleep apnea (OSA) and can persist despite use of positive airway pressure (PAP) therapy. These analyses assessed relationships between EDS, PAP use, and patient satisfaction across several aspects of OSA care in a real-world population with OSA. Methods: US residents (aged ≥18 years, self-reported physician OSA diagnosis [1/1/2015–3/31/2020]) completed a survey in Evidation Health's Achievement app assessing Epworth Sleepiness Scale (ESS), PAP usage, and satisfaction with care. Self-reported PAP use was categorized as nonuse, nonadherent (<4 h/night; <5 d/wk), intermediate (4–6 h/night, ≥5 d/wk), or highly adherent (≥6 h/night, ≥5 d/wk) (PAP-adherent=intermediate and highly adherent groups). Logistic regression models assessed impacts of PAP adherence and EDS on satisfaction with care across 7 domains. P-values are uncontrolled for multiplicity (nominal). Results: Among all participants (N=2289; 50.3% female, 82.5% White, 44.8±11.1 years old [mean±SD], 35.4±8.7 kg/m2 body mass index [mean±SD]), 42.5% had EDS (ESS>10). PAP use was: nonuse (n=700), nonadherent (n=153), or adherent (n=1436; intermediate n=225, high n=1211). Within these subgroups, the proportions (95% CI) with EDS were: nonuse (47% [43.7–51.1]), nonadherent (52% [44.4–60.2]), intermediate (53% [46.4–59.4]), and highly adherent (36% [33.7–39.1]). Logistic regression (using data from PAP users) showed a positive association of PAP adherence with satisfaction with PAP (OR [95% CI]: 5.43 [3.73–7.90]); OSA treatment effectiveness (3.56 [2.48–5.12]); OSA symptom management (3.15 [2.17–4.57]); coordination of OSA care (2.60 [1.82–3.72]); and education from their healthcare provider on the impact of OSA on cardiovascular health (1.62 [1.13–2.35]), importance of using PAP (1.7 [1.15–2.52]), or availability of prescription drugs to treat OSA symptoms (1.55 [1.06–2.26]). The presence of EDS was associated with lower patient satisfaction in nearly all domains examined (ORs ranged from 0.44–0.62 across 6 of 7 domains). Conclusion: EDS was common in this real-world population with OSA, even among participants who were highly adherent PAP users. PAP adherence was associated with higher patient satisfaction across all care domains; the presence of EDS was associated with lower patient satisfaction across 6 of 7 domains. Support (If Any): Jazz Pharmaceuticals